A fable of bees and gravity - Rauch, F (University of Oxford, 2014)
Gravity equations in trade imply that trade flows are proportional to the size of a country and inversely proportional to distance. This paper develops an analogy of these observations with gravity in physics, and provides geometric intuition for a large class of mathematical processes in two dimensional space for which these relationships would be expected. It then gives examples of trade processes that conform to gravity, including foraging patterns of various animal species.